Emerging chemotherapy-based treatments in anaplastic thyroid cancer: an updated analysis of prospective studies - Wang, Bi-Cheng; Lin, Guo-He; Kuang, Bo-Hua; Cao, Ru-Bo (Frontiers in Endocrinology, 2024)
Background: For anaplastic thyroid cancer (ATC) patients without mutational driver genes, chemotherapy is suggested to be the first-line treatment option. However, the benefits of chemotherapy in treating ATC are limited. In this analysis, we collected the prospective data reported since 2010 to analyze the emerging chemotherapy-based treatments in ATC comprehensively. Methods: For this updated analysis, we searched PubMed (MEDLINE), Web of Science, Embase, and Cochrane CENTRAL databases from Jan 01, 2010, until Feb 07, 2024, for prospective clinical studies that contained chemotherapy-based treatments.This analysis was done to pool overall survival (OS), progression-free survival (PFS), objective response rates (ORRs), disease control rates (DCRs), and grade 3 or worse treatment-related adverse events (TRAEs).Results: Six prospective clinical trials with 232 patients were included. Chemotherapy was commonly combined with targeted therapy or radiotherapy. The pooled median OS was 6.0 months (95% CI 4.1-9.7), and the median PFS was 3.2 months (95% CI 1.9-6.0) in ATC patients who received chemotherapy-based strategies. The integrated ORR and DCR were 21% (95% CI 15%-27%) and 64% (95% CI 55%-72%), respectively.Regarding the grade 3 or worse TRAE, the pooled incidence was 68% (95% CI 47%-86%).Although the emerging chemotherapy-based treatments showed antitumor activity in patients with ATC, these strategies failed to prolong the survival time substantially. More practical, safe, and novel therapeutic regimens for ATC patients warrant further investigations.